Decontamination of titanium implants using physical methods. Issue 8 (8th July 2016) - Al‐Hashedi, Ashwaq A.; Laurenti, Marco; Benhamou, Veronique; Tamimi, Faleh
Abstract: Objectives: Current decontamination methods of titanium (Ti) implant present limited success in achieving predictable re‐osseointegration. We hypothesized that even though these techniques could be useful in elimination of bacteria, they might be unsuccessful in removing organic contaminants and restoring the original surface composition. The aim of this study was to assess the effect of four decontamination methods on the surface chemistry and bacterial load of biofilm‐contaminated implant surfaces in order to improve implant surface decontamination. Material and methods: The ability of clinically available methods such as metal and plastic curettes, Ti brushes and Er: YAG laser to decontaminate Ti implant surfaces was assessed. Surface morphology, chemical composition and properties of machined Ti discs (Ø 5.0 and 1.0 mm thick) were analysed before and after oral biofilm contamination using scanning electron microscope and X‐ray photoelectron spectroscopy. The presence and viability of bacteria were evaluated with live–dead assays. Results: Biofilm contamination created an organic layer rich in hydrocarbons and bacteria that covered entirely the Ti surfaces. This organic layer has tightly adhered to Ti surfaces and could not be completely removed with any of the methods assessed. Ti brushes achieved greater elimination of organic contaminants and bacteria than curettes and Er: YAG laser; however, none of them was able to restore the original surface chemistry. Alternatively, Er: YAG laser‐treated surfaces showed the lowest live‐to‐dead bacterial ratio. Conclusions: Ti brushes were more effective than curettes (metal or plastic) and Er: YAG laser in decontaminating Ti implant surfaces, although none of these techniques was able to completely eliminate surface contamination. Er: YAG laser was more effective than curettes and Ti brushes in killing the biofilm bacteria.